Maenlich. Weiblich. Zur Bedeutung der Kategorie Geschlecht in der Kultur, hrsg. Christel Koehle-Hezinger, Martin Scharfe, Rolf Wilhelm Brednich, Waxmann, Muenster, New York, Muenchen, Berlin 1999., 540 str - Čale Feldman, Lada (Array, 2000)
Prikaz knjige.